Wasteland Mapping, Analysis and Management of Sustainable Development of the Rushikulya Basin Using Remote Sensing Technique - Panda, Damodar (National Geographical Journal of India, 2022)
Wastelands are those lands which are either not available for cultivation or leftout without being cultivated like fallows and culturable waste. The wastelands are classified into culturable wastelands and unculturable wastelands. The mapping of the wastelands are done using Remote Sensing technique. The various wastelands found in the basin consist of areas of shifting cultivation, deforestations, overgrazing ,water logging, intrusion of saline water etc. Out of the total wastelands, culturable wastelands account for 88.79 percent and unculturable wastelands 11.21 percent. Hence steps need to be taken to reclaim the culturable wastelands for sustainable development of the basin.